Antecedents of using electronic money application on technology communication during covid-19 pandemi - Atmaja, Ni Putu Cempaka Dharmadewi; Dwi Puspitawati, Ni Made (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
This paper aims to evaluate and discover the effect of perceived ease of use, perceived usefulness, attitude, and e-money applications use. The research data comprised primary data obtained from online questionnaires, distributed to 100 respondents of e-money users selected with a purposive sampling method. Aided with AMOS analysis tools, the Structural Equation Modeling (SEM) was employed for the data analysis. Findings revealed that perceived ease of use had significant effects on 1) perceived usefulness, and 2) the use of e-money applications. Perceives usefulness significantly affects attitude. Attitude has significant influences on the use of e-money applications. Also, perceived fully mediates on the effect of perceived ease of use on attitude. The effect of perceived usefulness on the use of e-money applications is fully mediated by attitude as the mediator. Besides, the effect of perceived ease of use on attitude is statistically non-significant, implying that it does not mediate the effect of perceived ease of use on the use of e-money applications.